2006
DOI: 10.1590/s0100-84042006000300005
|View full text |Cite
|
Sign up to set email alerts
|

Polinização por beija-flores em uma área de caatinga no Município de Floresta, Pernambuco, Nordeste do Brasil

Abstract: -(Pollination by hummingbirds in a "caatinga" area in Pernambuco State, northeastern Brazil). Ornithophilous plants were studied in a caatinga area (8º36'00" S and 38º34'5" W) in the State of Pernambuco, Northeast of Brazil, from July 2002 to June 2003. Eight ornithophilous species, belonging to five families and seven genera, were registered in the studied community. Cactaceae was the most representative family, with three species pollinated by hummingbirds, followed by Bromeliaceae with two species. Exceptin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0
26

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 38 publications
3
32
0
26
Order By: Relevance
“…São poucos os estudos que contemplam os ciclos sazonais destas comunidades (e.g. FISCHER & ARAUJO 1995, SAZIMA et al 1996, BUZATO et al 2000, ARAUJO & SAZIMA 2003, KAEHLER et al 2005, LEAL et al 2006, MACHADO & SEMIR 2006, MACHADO et al 2007.…”
unclassified
See 1 more Smart Citation
“…São poucos os estudos que contemplam os ciclos sazonais destas comunidades (e.g. FISCHER & ARAUJO 1995, SAZIMA et al 1996, BUZATO et al 2000, ARAUJO & SAZIMA 2003, KAEHLER et al 2005, LEAL et al 2006, MACHADO & SEMIR 2006, MACHADO et al 2007.…”
unclassified
“…MACHADO & SAZIMA 1995, MACHADO & LOPES 2002, 2004, LEAL et al 2006, COLAÇO et al 2006, MACHADO et al 2007. Na Chapada Diamantina, porção norte da Cadeia do Espinhaço, no Estado da Bahia, apesar da riqueza de tipos vegetacionais, da grande diversidade e do elevado endemismo de espécies vegetais (GIULIETTI et al 1997, JUNCÁ et al 2005, as investigações sobre este tipo de interação somente foram conduzidas em áreas de campo rupestre (COLAÇO et al 2006, MACHADO et al 2007.…”
unclassified
“…Studies concerning seasonality of A. gounellei reported the species on caatinga and humid vegetation in both dry and rainy seasons, as well as resident and occasional (Olmos, 1993;Santos, 2004;Leal et al, 2006;Santos et al, 2012;Silva et al, 2012;Silveira & Santos, 2012;Ruiz-Esparza et al, 2015). We found only one seasonality record for cerrado-like vegetation which reported A. gounellei as occasional on an area close to caatinga, and during a severe drought (Machado, 2014).…”
Section: Environmental Conditionsmentioning
confidence: 54%
“…Humid vegetation also appeared in lowlands (Silva, 2009;Silva et al, 2012;Ruiz-Esparza et al, 2015). However, the majority of vegetation recorded belongs to the caatinga type, ranging from shrubby caatinga to dense arboreal caatinga Olmos et al, 2005;Leal et al, 2006;Vasconcelos et al, 2006;Farias, 2007;Araujo et al, 2012;Olmos & Albano, 2012); cerrado and rocky fields were also reported but in a small number (Dornelas et al, 2012;Machado, 2014;Pereira et al, 2014).…”
Section: Environmental Conditionsmentioning
confidence: 99%
“…virens embora tenham sido baixos, estão de acordo com o encontrado para espécies ornitófilas (Sazima et al 1996;Buzato et al 2000;Leal et al 2006). Essa baixa produção de néctar registrada pode representar uma estratégia para que os animais precisem visitar flores de outros indivíduos em busca de mais recursos gerando com isso, um grande movimento entre os indivíduos da mesma espécie e promovendo a polinização cruzada, principalmente para as espécies que apresentam heterostilia, como é o caso de Psychotria spectabilis.…”
Section: Características Floraisunclassified